Lay theories of self‐control influence judgments of individuals who have failed at self‐control. Issue 7 (26th June 2013) - Freeman, Nicholas; Shmueli, Dikla; Muraven, Mark
Abstract Individuals who have failed at self‐control are often the targets of negative social judgments. We suggest that in some circumstances, individual differences in lay theories regarding self‐control may help account for these reactions. Specifically, people may believe that the ability to exert self‐control is either a fixed quantity (entity theory) or a malleable quantity (incremental theory), and these beliefs may influence their social judgments. In the current investigation, we found that whether lay theories of self‐control were measured or manipulated, entity views of self‐control predicted more negative judgments about a target whose self‐control failure was made salient.